DIMENSIONS OF TOURISM DEVELOPMENT: TOURISM STRATEGIES AND PERFORMANCE INDICATORS (CASE STUDY IN PARIAMAN CITY) - Yuliviona, Reni; Zaitul, Zaitul; Husna, Radiatul; Kamener, Dahliana (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to examine the development of tourism strategies and performance indicators in Pariaman City West Sumatra. The data used primary data that was obtained through focus group discussions and limited interviews with relevant informants, while the quantitative method used primary data was obtained through surveys and secondary data. The sample technique was the census method with 390 respondents. The data was processed using structural equation modelling with Smart-PLS 3.0 software. The research concluded that the city of Pariaman has adequate tourist destinations which are important factors in determining tourist satisfaction and intent to revisit in the future. The research showed Tourist image, reliability, and responsiveness affect significantly tourist satisfaction. Besides, tourist satisfaction affects significant on intention to revisit. Keywords: Performance, Strategy, Satisfaction, Intention to Return